Progress Of Poliomyelitis Control Selected States And Union Territories - Sokhey Jotna (Wolters Kluwer Medknow Publications, 1992)
Goa, Haryana, Himachal Pradesh, Karnataka, Kerala, Maharashtra, Punjab, Tamil Nadu, Chandigarh and Pondicherry have recorded sustained high levels of coverage with the third dose of oral polio vaccine (OPV) over the last few years. An incidence rate of poliomyelitis of 1.1/100,000 populations was recorded in these states in 1990, a decline of more than 80% as compared to the reported incidence of 5.7/100,000 populations in 1980. The efficacy of OPV in the control of poliomyelitis is convincingly documented by the decline in cases despite several measures taken to strengthen the surveillance system. The impact has been recorded in widely diverse; areas such as the hitty terrain in Himachal Pradesh to high-density areas in Bombay and Madras were large proportion of the population live under poor sanitary conditions. The data shows that the strategy of progressively increasing coverage through regular immunization services, as part of primary health care, is effective.